An epistemological approach to emotional competences in wrestling coaches (Revista científica Olimpia, 2015)
The research has been based in revealing the epistemological statements about the emotional competence in wrestling coaches while managing the athletes training and athletic competitions, because the lack of these generate unsportsmanlike behavior which affects the proper development of the sport activity. From this problem, it is arisen the aim of this article in stating a theoretical outline on the psychological thought trends, that have dealt with the topic, used for addressing the need to clarify viewpoints and ideas about the emotional component in the psychological preparation of sport professionals and coaches. From this systematization was displayed a set of ideas that will help to establish an epistemological frame where emotional competences are assumed as self-referent in the  development of personality; among those were proposed: self-awareness, emotional self-control, self-esteem and assertiveness. From the literature review, a set of methods are suggested to obtain the updated diagnosis of emotional competences in wrestling coaches. Also, psychological intervention techniques have come up in order to modify the behavior of coaches through the development of these sport activities, these theoretical underpinnings constitute the conceptual basis for proposing a program of Psycho-educational Intervention to encourage these skills in wrestling coaches.
Keywords: emotional competence; self-control; self-awareness; emotional intelligence; wrestling coaches; sport training